Martin R. Delany's Civil War and Reconstruction : a primary source reader - Adeleke, Tunde (University Press of Mississippi, 2020)
"To engage Martin Robison Delany (1812-1885) is to wrestle with almost all the complexities and paradoxes of nineteenth-century black leadership in one public intellectual. After his previous book on Delany, senior historian Tunde Adeleke has compiled here letters, speeches, contemporary nineteenth-century newspaper articles, and reports written by and about Delany. These vital primary sources cover his Civil War and Reconstruction career in South Carolina and include key critical reactions to Delany's ideas and writings from his contemporaries. There are over ninety documents, the vast majority not previously published"